Copy-number-aware differential analysis of quantitative DNA sequencing data - Robinson, Mark D.; Strbenac, Dario; Stirzaker, Clare; Statham, Aaron L.; Song, Jenny; Speed, Terence P.; Clark, Susan J. (Genome Research, 2012)
Developments in microarray and high-throughput sequencing (HTS) technologies have resulted in a rapid expansion of research into epigenomic changes that occur in normal development and in the progression of disease, such as cancer. Not surprisingly, copy number variation (CNV) has a direct effect on HTS read densities and can therefore bias differential detection results. We have developed a flexible approach called ABCD-DNA (affinity-based copy-number-aware differential quantitative DNA sequencing analyses) that integrates CNV and other systematic factors directly into the differential enrichment engine.
10.1101/gr.139055.112